Inhibition of Neutrophil Functions and Antibacterial Effects of Tarragon (Artemisia dracunculus L.) Infusion—Phytochemical Characterization - Majdan, Magdalena; Kiss, Anna K.; Hałasa, Rafał; Granica, Sebastian; Osińska, Ewa; Czerwińska, Monika E. (Frontiers in Pharmacology, 2020)
The aim of the study was a characterization of phytochemicals in an infusion of aerial part of tarragon (Artemisia dracunculus L.) using UHPLC‐DAD‐ESI‐MS/MS method, as well as an evaluation of its effects on mediators of the inflammation in an in vitro model of human neutrophils, and antimicrobial activity on selected pathogens. Flavonoids and caffeoylquinic acids were the main phenolic components of the extract of tarragon aerial part . The infusion was able to inhibit reactive oxygen species (ROS), interleukin 8 (IL-8) and TNF-α (tumour necrosis factor) production. The antimicrobial assay was performed with the use of nine strains of bacteria, both Gram-negative and Gram-positive. Three human pathogens, such as Staphylococcus aureus ATCC6538, Staphylococcus epidermidis ATCC14990 and Staphylococcus aureus MRSA ATCC43300, proved to be the most sensitive to tarragon infusion. Our study demonstrated the antiinflammatory and antimicrobial properties and therefore the common spice, tarragon (Artemisia dracunculus L.) may be a prospective source of health promoting constituents.